Vegetation classification and biogeography of European floodplain forests and alder carrs - Douda, Jan; Boublík, Karel; Slezák, Michal; Biurrun, Idoia; Nociar, Josef; Havrdová, Alena; Doudová, Jana; Aćić, Svetlana; Brisse, Henry; Brunet, Jörg; Chytrý, Milan; Claessens, Hugues; et al. (Applied vegetation science, 2016)
AIM: Formalized classifications synthesizing vegetation data at the continental scale are being attempted only now, although they are of key importance for nature conservation planning. Therefore, we aim to provide a vegetation classification and to describe the main biogeographical patterns of floodplain forests and alder carrs in Europe. LOCATION: Europe. METHODS: A database of more than 40 000 vegetation plots of floodplain forests and alder carrs across Europe was compiled. After geographic stratification, 16 392 plots were available for classification, which was performed using the supervised method Cocktail. We also searched for new associations using semi‐supervised K‐means classification. The main biogeographic patterns and climate‐related gradients in species composition were determined using detrended correspondence analysis and cluster analysis. RESULTS: Thirty associations of floodplain forests and alder carrs were distinguished, which belong to five alliances. The Alnion incanae includes riparian, seepage and hardwood floodplain forests in the nemoral and hemiboreal zones (dominated by Alnus glutinosa and Fraxinus excelsior) and in the boreal zone (dominated by A. incana). The Osmundo‐Alnion represents oceanic vegetation dominated by Alnus glutinosa, Fraxinus angustifolia and F. excelsior distributed mostly on the Iberian Peninsula and composed of species with Atlantic distribution and Iberian endemics. The Populion albae comprises floodplain forests frequently dominated by Fraxinus angustifolia, Populus alba and P. nigra that are widespread in floodplains of large rivers under summer‐dry climates in the Mediterranean region. The Platanion orientalis represents eastern Mediterranean floodplain forests dominated by Platanus orientalis. The Alnion glutinosae includes forest swamps dominated by Alnus glutinosa distributed mostly in the nemoral and hemiboreal zones. The main biogeographic patterns within European floodplain forests and alder carrs reflect the climatic contrasts between the Mediterranean, nemoral, boreal and mountain regions. Oceanic floodplain forests differ from those in the rest of Europe. The hydrological regime appears to be the most important factor influencing species composition within regions. CONCLUSIONS: This study is the first applying a formalized classification at the association level for a broad vegetation type at the continental scale. The proposed classification provides the scientific basis for the necessary improvement of the habitat classification systems used in European nature conservation.